Examining motivation profile differences across students’ mathematics identity, performance, and parents’ attitudes - Ilomanni, Pia; Radišić, Jelena; Laine, Anu (LUMAT: International Journal on Math, Science and Technology Education, 2025)
Declining development in Finnish students’ mathematics performance has highlighted the importance of mathematics competence and motivation research. We used the person-centred approach to investigate Finnish third-, fourth-, and fifth-grade students’ mathematics motivation profiles. In addition, we explored differences between the motivation profiles regarding students’ mathematics identity, performance, and their parents’ mathematics-related attitudes. A latent profile analysis (LPA) based on 304 third-, fourth-, and fifth-grade students’ answers revealed three math-related motivation profiles: high motivation, high cost and moderate. Further investigation of the profiles showed that students’ higher mathematics identity is represented strongly in the high motivation group, as are students’ mathematics performance scores. Parents perceived low mathematics competence as highly expressed in those students belonging to the high cost profile. Results concerning students’ broader learning environment and previous results relevant to the Finnish educational system are discussed. Updates 2025-01-07: Project name added to page 7.